The Effect Brand Awareness And Brand Equity On The Buying Decisions (Survey on consumers of Honda Beat Tasikmalaya City) - Sobariah, Iis Aisyah; Pauzy , Depy Muhamad; Arif, Arif (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The purpose of this study is to determine the effect of brand awareness and brand equity on the buying decision to the Honda Beat Tasikmalaya city.The research method used is a questionnaire method with a survey approach of 100 respondents who are consumers of Honda Beat. The types of data used are primary data and secondary data. The data analysis technique used is multiple regression analysis. The results of this test prove that brand awareness and brand equity have a significant effect both partially and simultaneously on the buying decision consumers Honda Beat Tasikmalaya city.